Relationship Between Smoking Level, Coffee Consumption, and Sleep Quality with Dyspepsia Syndrome Occurrence in Mataram City Regional Public Hospital - Syah Jihan Mastanderman; Deny Sutrisna Wiatma; Velia Maya Samoedra; IGP Winangun (Jurnal Biologi Tropis, 2026)
Dyspepsia syndrome is a prevalent health issue that can disrupt daily routines and diminish overall productivity. This study aims to evaluate the correlation between smoking intensity, coffee intake, and sleep quality with the occurrence of dyspepsia syndrome at the Mataram City Regional General Hospital (RSUD). Utilizing an analytical observational method with a cross-sectional framework, this quantitative research involved a sample of 107 patients selected via simple random sampling. Data analysis was conducted through univariate and bivariate methods using the Chi-square test. The findings reveal a statistically significant association between smoking degree (p=0.000) and coffee consumption (p=0.000) with the incidence of dyspepsia. In contrast, no significant relationship was observed regarding sleep quality (p=0.348). In summary, smoking habits and coffee consumption are major contributors to dyspepsia syndrome, whereas sleep quality is not a primary factor. Future studies are encouraged to investigate additional variables, such as psychological stress and dietary patterns, to provide a more comprehensive understanding of dyspepsia risk factors.